Outcomes in very low birthweight infants with severe congenital heart defect following cardiac surgery within the first year of life. (24th November 2021) - Boos, Vinzenz; Berger, Felix; Cho, Mi-Young; Photiadis, Joachim; Bührer, Christoph; Pfitzer, Constanze
Abstract: OBJECTIVES: Very low birthweight (<1500 g, VLBW) infants with severe congenital heart defect (CHD) are at increased risk for perinatal and operative mortality. This study aims to describe morbidity, long-term mortality and neuro-developmental outcome in early childhood in VLBW infants who received cardiac surgery for severe CHD within 1 year after birth. METHODS: Monocentric observational study on VLBW infants with severe CHD born between 2008 and 2017. Neurodevelopmental impairment at 2 years corrected age was defined as cognitive deficit, cerebral palsy or major neurosensory deficit. RESULTS: A total of 24 patients were included. Twenty-one (87.5%) infants underwent cardiac surgery with hypothermia during cardiopulmonary bypass (median temperature 30.3°C, interquartile range 27.0–32.0°C) at a median age of 96 (40–188) days. Seven (29.2%, 95% confidence interval 14.9–49.2%) patients died within the first year after cardiac surgery. Survival rates decreased with increasing STAT mortality category of the surgical procedure. Neurodevelopmental impairment at 2 years of corrected age was found in 9 out of 17 (52.9%) surviving infants, with 8 infants (47.1%) presenting with a cognitive deficit or delay and 4 infants (23.5%) being diagnosed with cerebral palsy. Survival without neuro-developmental impairment was 29.2% ( n = 7, 95% confidence interval 14.9–49.2%) in the entire study cohort. Eighty percent of the newborns with dextro-transposition of the great arteries, but no patient with univentricular anatomy, survived without neuro-developmental impairment. CONCLUSIONS: Individual VLBW infants with severe CHD may develop well despite the high combined risk for adverse outcomes. The type of cardiac malformation may affect early- and long-term outcomes. Abstract : Congenital malformations and low birthweight are leading causes of infant mortality [1].